Changes in smoking behavior among victims after the great East Japan earthquake and tsunami - Yoneatsu Osaki; Hitoshi Maesato; Ruriko Minobe; Aya Kinjo; Yuki Kuwabara; Aya Imamoto; Yoshinori Myoga; Sachio Matsushita; Susumu Higuchi (Komiyama Printing Co. Ltd, 2020)
Abstract Background In areas affected by the tsunami of the great East Japan Earthquake, smoking behavior may have deteriorated due to high stress and drastic changes in living environment. Surveys were conducted to reveal changes in smoking behaviors among victims. Methods A population-based random-sample home-visit interview survey of victims in Iwate and Miyagi Prefectures affected by the tsunami disaster was conducted in 2012 (n = 1978), while a population-based nationwide survey was conducted in 2013 (n = 1082). A panel survey in 2014 was conducted with respondents of the 2012 survey (n = 930). Multiple logistic regression analysis was performed to reveal factors related to smoking status after the disaster. Results There was high smoking prevalence of both sexes in the tsunami disaster area (current smoking rate in coastal area, 50.0% for male, 21.4% for female; inland area, 34.7% for male, 7.6% for female). Low prevalence of male quitters was observed (quitter rate in coastal area, 20.8% for male, 8.0% for female; inland area, 23.4% for male, 5.5% for female). The prevalence of nicotine-dependent people assessed by FTND (Fagerström Test for Nicotine Dependence) in the coastal area was also higher than in the inland area or other areas of Japan. Smoking behavior among victims worsened after the disaster and did not improve 3 years from the disaster. Post-disaster factors related to smoking were living in coastal area, complete destruction of house, and living in temporary housing. Conclusions Smoking prevalence and the level of nicotine dependence of tsunami victims were still high even 3 years after the disaster. It is important to emphasize measures for smoking control in the disaster areas for an extended time period.